Mobility Skills With Exoskeletal-Assisted Walking in Persons With SCI: Results From a Three Center Randomized Clinical Trial - Hong, EunKyoung; Gorman, Peter H.; Forrest, Gail F.; Asselin, Pierre K.; Knezevic, Steven; Scott, William; Wojciehowski, Sandra Buffy; Kornfeld, Stephen; Spungen, Ann M. (Frontiers in Robotics and AI, 2020)
Background: Clinical exoskeletal-assisted walking (EAW) programs for individuals with spinal cord injury (SCI) have been established, but many unknown variables remain. These include addressing staffing needs, determining the number of sessions needed to achieve a successful walking velocity milestone for ambulation, distinguishing potential achievement goals according to level of injury, and deciding the number of sessions participants need to perform in order to meet the Food and Drug Administration (FDA) criteria for personal use prescription in the home and community. The primary aim of this study was to determine the number of sessions necessary to achieve adequate EAW skills and velocity milestones, and the percentage of participants able to achieve these skills by 12 sessions and to determine the skill progression over the course of 36 sessions. Methods: A randomized clinical trial (RCT) was conducted across three sites, in persons with chronic (≥6 months) non-ambulatory SCI. Eligible participants were randomized (within site) to either the EAW arm first (Group 1), three times per week for 36 sessions, striving to be completed in 12 weeks or the usual activity arm (UA) first (Group 2), followed by a crossover to the other arm for both groups. The 10-meter walk test (s) (10MWT), 6-minute walk test (m) (6MWT), and the Timed-Up-and-Go (s) (TUG) were performed at 12, 24 and 36 sessions. To test walking performance in the exoskeletal devices, nominal velocities and distance milestones were chosen prior to study initiation were used for the 10MWT (≤40s), 6MWT (≥80m) and TUG (≤90s). All walking tests were performed with the exoskeletons. Results: A total of 50 participants completed 36 sessions of EAW training. At 12 sessions, 31 (62%), 35 (70%) and 36 (72%) participants achieved the 10MWT, 6MWT and TUG milestones respectively. By 36 sessions, 40 (80%), 41 (82%) and 42 (84%) achieved the 10MWT, 6MWT, and TUG criteria respectively. Conclusions: It is feasible to train chronic non-ambulatory SCI individuals in performance of EAW sufficiently to achieve reasonable mobility skill outcome milestones.